Using museum specimens of northern shortfin squid (Illex illecebrosus) to evaluate long-term ecological changes in the Northeast U.S. Continental Shelf large marine ecosystem - Valerie H. Dimkovikj; Michelle D. Staudinger; Henry D. Legett; Christine A. M. France; Michael Vecchione (Marine Biology, 2025)

Ten best practices for effective phenological research - Richard B. Primack; Amanda S. Gallinat; Elizabeth R. Ellwood; Theresa M. Crimmins; Mark D. Schwartz; Michelle D. Staudinger; Abraham J. Miller-Rushing (International Journal of Biometeorology, 2023)
The number and diversity of phenological studies has increased rapidly in recent years. Innovative experiments, field studies, citizen science projects, and analyses of newly available historical data are contributing insights that advance our understanding of ecological and evolutionary responses to the environment, particularly climate change. However, many phenological data sets have peculiarities that are not immediately obvious and can lead to mistakes in analyses and interpretation of results. This paper aims to help researchers, especially those new to the field of phenology, understand challenges and practices that are crucial for effective studies. For example, researchers may fail to account for sampling biases in phenological data, struggle to choose or design a volunteer data collection strategy that adequately fits their project’s needs, or combine data sets in inappropriate ways. We describe ten best practices for designing studies of plant and animal phenology, evaluating data quality, and analyzing data. Practices include accounting for common biases in data, using effective citizen or community science methods, and employing appropriate data when investigating phenological mismatches. We present these best practices to help researchers entering the field take full advantage of the wealth of available data and approaches to advance our understanding of phenology and its implications for ecology.

The North American Freshwater Migratory Fish Database ( NAFMFD ): Characterizing the migratory life histories of freshwater fishes of Canada, the United States and Mexico - Emily M. Dean; Arthur R. Cooper; Lizhu Wang; Wesley Daniel; Solomon David; Clayton Ernzen; Keith B. Gido; Edward Hale; Tim J. Haxton; William Kelso; Nancy Leonard; Chris Lido; et al. (Journal of Biogeography, 2022)
Aim Migratory freshwater fishes are those that must access discrete habitats to complete their life cycles. Freshwater fish migrations occur around the world and provide numerous ecosystem services for humans and natural systems; however, many migratory species are in decline globally. A limiting factor to successfully conserve freshwater migratory fishes is that the migratory life histories of many species are unknown or only partially described. To provide researchers with critical and comprehensive information to conserve migratory fishes, we developed the North American Freshwater Migratory Fish Database (NAFMFD). Location Canada, Mexico and the United States. Taxon Freshwater fish. Methods To develop this database, we assigned migratory status, pattern and behaviour to a comprehensive list of freshwater fish species found throughout North America. We assembled the database which included assignments (i.e. migratory status, pattern and behaviour) as well as the sources used to make the assignments. Researchers and managers from across North America reviewed the database for completeness and accuracy on the migratory life histories of fishes. Results The database synthesizes current knowledge of migratory status, pattern and behaviour of native and non‐native freshwater fishes throughout North America, including 1250 species representing 79 families and 325 genera. Results showcase the diversity of migratory life histories of freshwater fishes on the continent, including that at least 25% of North American freshwater fishes are migratory, 23% are non‐migratory and 44% have undetermined migratory status. Main conclusions NAFMFD improves the quality of migratory data accessible to researchers, which supports a more holistic understanding of the threats encountered by migratory fishes, including habitat fragmentation. The approach we used in developing NAFMFD can provide guidance for developing similar databases in other regions. Collectively, our work offers new insights into the range of freshwater fish migratory life histories, stimulating a need to better understand this diversity globally.

Leaf manganese concentrations as a tool to assess belowground plant functioning in phosphorus-impoverished environments - Hans Lambers; Ian J. Wright; Caio Guilherme Pereira; Peter J. Bellingham; Lisa Patrick Bentley; Alex Boonman; Lucas A. Cernusak; William Foulds; Sean M. Gleason; Emma F. Gray; Patrick E. Hayes; Robert M. Kooyman; et al. (Plant and Soil, 2021)

It’s about time: A synthesis of changing phenology in the Gulf of Maine ecosystem - Michelle D. Staudinger; Katherine E. Mills; Karen Stamieszkin; Nicholas R. Record; Christine A. Hudak; Andrew Allyn; Antony Diamond; Kevin D. Friedland; Walt Golet; Meghan Elisabeth Henderson; Christina M. Hernandez; Thomas G. Huntington; et al. (Fisheries Oceanography, 2019)
The timing of recurring biological and seasonal environmental events is changing on a global scale relative to temperature and other climate drivers. This study considers the Gulf of Maine ecosystem, a region of high social and ecological importance in the Northwest Atlantic Ocean and synthesizes current knowledge of (a) key seasonal processes, patterns, and events; (b) direct evidence for shifts in timing; (c) implications of phenological responses for linked ecological‐human systems; and (d) potential phenology‐focused adaptation strategies and actions. Twenty studies demonstrated shifts in timing of regional marine organisms and seasonal environmental events. The most common response was earlier timing, observed in spring onset, spring and winter hydrology, zooplankton abundance, occurrence of several larval fishes, and diadromous fish migrations. Later timing was documented for fall onset, reproduction and fledging in Atlantic puffins, spring and fall phytoplankton blooms, and occurrence of additional larval fishes. Changes in event duration generally increased and were detected in zooplankton peak abundance, early life history periods of macro‐invertebrates, and lobster fishery landings. Reduced duration was observed in winter–spring ice‐affected stream flows. Two studies projected phenological changes, both finding diapause duration would decrease in zooplankton under future climate scenarios. Phenological responses were species‐specific and varied depending on the environmental driver, spatial, and temporal scales evaluated. Overall, a wide range of baseline phenology and relevant modeling studies exist, yet surprisingly few document long‐term shifts. Results reveal a need for increased emphasis on phenological shifts in the Gulf of Maine and identify opportunities for future research and consideration of phenological changes in adaptation efforts.

A review of coastal management approaches to support the integration of ecological and human community planning for climate change - Emily J. Powell; Megan C. Tyrrell; Andrew Milliken; John M. Tirpak; Michelle D. Staudinger (Journal of Coastal Conservation, 2019)

Atlantic bluefin tuna Thunnus thynnus feeding ecology in the northern Gulf of Mexico: a preliminary description of diet from the western Atlantic spawning grounds - C. M. Butler; J. M. Logan; J. M. Provaznik; E. R. Hoffmayer; M. D. Staudinger; J. M. Quattro; M. A. Roberts; G. W. Ingram; A. G. Pollack; M. E. Lutcavage (Journal of Fish Biology, 2015)
A combination of stomach contents, nitrogen stable‐isotope and tissue C:N values are presented to demonstrate feeding activity of Atlantic bluefin tuna Thunnus thynnus on the Gulf of Mexico (GOMEX) spawning grounds. Diets include teleosts, cephalopods, crustaceans and a pelagic tunicate ( Pyrosoma atlanticum ). Results reveal the need to classify the GOMEX as a T. thynnus feeding ground.

Ethical and welfare considerations when using cephalopods as experimental animals - N. A. Moltschaniwskyj; K. Hall; Marek R. Lipinski; J. E. A. R. Marian; M. Nishiguchi; M. Sakai; D. J. Shulman; B. Sinclair; D. L. Sinn; M. Staudinger; R. Van Gelderen; R. Villanueva; et al. (Reviews in Fish Biology and Fisheries, 2007)

Electroporation of isolated higher-plant mitochondria: transcripts of an introduced cox2 gene, but not an atp6 gene, are edited in organello - M. Staudinger; F. Kempken (Molecular Genetics and Genomics, 2003)

Spatial variability in the chemical composition of the snowcover at high alpine sites - W. Schner; H. Puxbaum; M. Staudinger; F. Maupetit; D. Wagenbach (Theoretical and Applied Climatology, 1997)